Situation and Life Quality of health of Myanmar migrant workers in Nakhon Si Thammarat Province: Situation and Health-Related Quality of Life of Myanmar Workers in Nakhon Si Thammarat Province - Khanamkhaew, Daycho (Journal of Health Sciences and Wellness, 2020)
This article aimed to study the health situation and health-related quality of life of Myanmar migrant workers in Nakhon Si Thammarat Province. Mixed methods, qualitative and quantitative, were carried out in this study. Two groups of samples were used where 21 key informants consisting of Myanmar workers, Thai friends, employers and government officers were used for the in-depth interview together with the observation by participation doing joint activities, such as playing sports and nonparticipation by outside the circle, not participating in activities and the descriptive analysis. Another group of samples consisted of 350 Myanmar workers was randomly selected and collected data using questionnaire. Data were then analyzed with statistical tools as frequency, percentage, mean and standard deviation. The findings indicated the following; (1) the situation of Myanmar workers in Nakhon Si Thammarat Province when it comes to health was having access to the health insurance system with a hospital nearest to their accommodation that can be used in times of sickness for consultation of any illness or disease, searching for the health care knowledge like playing sports to keep the body healthy and disease-free such as football, takraw or playing local sports. In addition, if they were stressed or uncomfortable, they would watch YouTube movies, and listen to music. (2) for the health-related quality of life of Myanmar workers in Nakhon Si Thammarat Province was, it was found at the medium level (x̄= 3.42, S.D.= 0.64).